Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2337/db06-1680
|View full text |Cite
|
Sign up to set email alerts
|

Direct Free Fatty Acid Uptake Into Human Adipocytes In Vivo

Abstract: We sought to assess whether direct uptake of circulating free fatty acids (FFAs) by adipocytes occurs in vivo in overnight postabsorptive humans and, if so, whether there are regional differences in uptake between lean and obese women and men. We used bolus injections of radiolabeled FFA tracers followed by carefully timed adipose tissue biopsies. First, we validated a method to measure direct adipocyte FFA uptake and then quantitated this process using the modified methods in normalweight postabsorptive men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
149
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 34 publications
(46 reference statements)
5
149
0
1
Order By: Relevance
“…This is the same pattern present in normal-weight women (15) and contrasts with the greater abdominal than femoral SA in normal-weight men (15).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…This is the same pattern present in normal-weight women (15) and contrasts with the greater abdominal than femoral SA in normal-weight men (15).…”
Section: Discussionmentioning
confidence: 76%
“…The relative storage of FFA via this direct pathway in upper versus lower body fat was consistent with sex-specific differences in body fat distribution, i.e., preferential upper body fat accumulation in men but not in women and greater total storage in subcutaneous fat of women. We estimated that this physiological process of FFA recycling independent of the VLDL-triglycerides/lipoprotein lipase (VLDL-TG/LPL) pathway might serve to redistribute fat from upper body stores to lower body stores in women but not men (15). Unfortunately, we had no information regarding the presence or absence of this process in visceral fat in humans.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…We also wanted to delineate if GPAT variations accounted for previously observed variations in adipose tissue fatty acid storage rates. 1,4,5,10 While GPAT is responsible for the first committed step of triacylglycerol (TAG) synthesis, diacylglycerol acetyl transferase (DGAT) is responsible for the final step of TAG synthesis: the conversion of diacylglycerols (DG) to TAG. 6 We have reported that DGAT activity correlates with rates of FFA storage in subcutaneous fat in some depots under some conditions.…”
Section: Introductionmentioning
confidence: 99%